DISEASES HIDDEN UNDER THE MASK OF DEPRESSION AND SOME CONSIDERATIONS FOR THEIR PREVENTION - KUBAYEV R.M; ABDURAZAKOVA R.Sh. (Scholar Express Journals, 2022)
This article discusses the diseases hidden under the guise of depression, ways to prevent them, depressive disorders accompanied by worsening psychoemotional state and their treatment.
Keywords: psycho-emotional; depression; psychiatrist; symptom